Irish-Type Zn-Pb Deposits Around the World 2023
DOI: 10.61153/zzug6529
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to Irish-type Zn-Pb deposits in early Cretaceous carbonate rocks of Iran

Abdorrahman Rajabi,
Pouria Mahmoodi,
Ebrahim Rastad
et al.

Abstract: Early Cretaceous carbonates are the most common host rocks for Irish-type deposits in Iran. They are largely concentrated in the Malayer-Esfahan metallogenic belt (MEMB) in southwestern Iran, and Yazd-Anarak metallogenic belt in Central Iran. They include some world‐class ore deposits such as Mehdiabad, Irankuh, and Ahangaran. These stratabound deposits are hosted mostly in carbonates with minor siltstones and volcanic components, that formed in extensional and passive margin environments that are related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Elsewhere in Europe bedded barite is associated with sediment-hosted Pb-Zn deposits in Germany (Meggen and Rammelsberg), Belgium (Chaudfontaine). The Cretaceous agreed Zn-Pb (±Ag±Ba) deposits in the Malayer-Esfahan Metallogenic belt of Iran have been described as Irish-type and have many features in common with Ballynoe (Silvermines) [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere in Europe bedded barite is associated with sediment-hosted Pb-Zn deposits in Germany (Meggen and Rammelsberg), Belgium (Chaudfontaine). The Cretaceous agreed Zn-Pb (±Ag±Ba) deposits in the Malayer-Esfahan Metallogenic belt of Iran have been described as Irish-type and have many features in common with Ballynoe (Silvermines) [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…More than 350 sediment-hosted Zn-Pb±Ag±Ba deposits have been reported in Iran (Rajabi et al, 2012a(Rajabi et al, , 2019aRajabi, 2022) occuring in a wide variety of siliciclastic and carbonate rocks from early Cambrian to Tertiary age (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Rajabi et al (2012a) suggested an Irish-type model for forming the Mehdiabad deposit. Based on geochemistry and geological evidence, Maghfouri et al (2019) suggested the sedimentary exhalative (Aghanabati, 1998) and distribution map of carbonate-hosted (MVT and Irish-type) Zn-Pb and F-rich deposits according to the age of host rocks in the Central Alborz, Tabas-Posht e Badam, Malayer-Esfahan, and Yazd-Anarak metallogenic belts (Rajabi et al, 2012a;2019a;2022). B) Simplified terrane map of the western Tethysides, and crustal domains of Iran (Rajabi et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%